Respon Pertumbuhan Stek Kayu Putih (Melaleuca cajuputi L.) Terhadap Perlakuan Hormon Dan Media Tanam Yang Berbeda : Response of Cajuput (Melaleuca cajuputi L.) Stem Cuttings to the Application of Different Hormones and Planting Media - Pareira, Magdalena Sunarty; Ceunfin, Maximus; Naikofi, Kristina Irnasari (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Cajuput (Melaleuca cajuputi L.) is a Multi-Purpose Tree Species (MPTS) with high economic and ecological value, yet propagation through seeds often encounters constraints related to seed viability and seedling uniformity. This study aimed to examine the effects of natural and synthetic plant growth regulators (PGRs) and growing media combinations on the growth performance of cajuput stem cuttings. The experiment was conducted at the experimental field of the Faculty of Agricultural Science and Health, University of Timor, using a factorial Completely Randomized Design (CRD) with two factors: types of PGR (Rootone F, shallot extract 15 mL/L, and aloe vera extract 15 mL/L) and media composition (soil:rice husk charcoal, soil:cow manure, and soil:rice husk charcoal:cow manure), each with three replications. Observed parameters included sprouting speed, shoot length, number of leaves, root length, and cutting mortality rate. The results showed a significant interaction between PGR type and media composition on sprouting speed at 10 weeks after planting (WAP), with the combination of shallot extract and soil:rice husk charcoal medium producing the best result. Aloe vera extract as a single treatment provided optimal growth for shoot length, leaf number, and root length, while also reducing cutting mortality compared to other treatments. Moreover, soil:rice husk charcoal medium generally supported better initial growth due to its high porosity and aeration. Therefore, the use of aloe vera extract combined with soil:rice husk charcoal medium is recommended as an effective approach for vegetative propagation of cajuput.